Pericarditis and Pleuritis Caused by Extramedullary Plasmacytoma - A. Samik Wahab; Sunarto Sunarto; Utomo Utomo (Paediatrica Indonesiana, 1990)
The following illustrates a case study of a 9 years-old girl with combined pericarditis and pleuritis caused by solitary extramedullary plasmacytoma. Pericardiocentesis and permanent thoracocentesis were performed, both yielded serohemorrhagic and serous fluid in succession. In the beginning etiological diagnosis was made on the basis of the clinical pattern for tuberculosis infection and growth of three species of bacteria for bacterial infections and candida species for candidiasis. The initial treatment was in accordance with the etiological diagnosis mentioned above. The final diagnosis was establish in the fourth month after the discovery of plasmacytoma in the pleural fluid and CT scan examination disclosing masses in the right lung. Accordingly, cytostatic therapy was started. The result of therapy was very good, exudation into the pleural and pericardia/ sac regressed gradually and eventually ceased completely. According to the literature the prognosis of these neop/asma is good.